2010 20th International Conference on Pattern Recognition 2010
DOI: 10.1109/icpr.2010.405
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of the Performance of Latent Fingerprint Recognition in Realistic Forensic Conditions

Abstract: Esta es la versión de autor de la comunicación de congreso publicada en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In recent years, palmprints have attracted more attention as a relevant and secure biometric method of personal identification, both in the civil and criminal fields. But while prints produced under controlled conditions, with ink or livescan methods provide high quality images (high‐resolution), although not always free of noises (disturbance of principal lines, wrinkles) that degrade the quality of some portions of the image, latent prints often give rise to low‐resolution images [30,32,33,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, palmprints have attracted more attention as a relevant and secure biometric method of personal identification, both in the civil and criminal fields. But while prints produced under controlled conditions, with ink or livescan methods provide high quality images (high‐resolution), although not always free of noises (disturbance of principal lines, wrinkles) that degrade the quality of some portions of the image, latent prints often give rise to low‐resolution images [30,32,33,37].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the extraction of stable and robust features from palmprints is still a problem, not only because of the low quality of the patterns of palmprints, but also because of the computational complexity for the large image size. Puertas et al [37] showed that the combination of manual matching done by an expert and the matching done by an AFIS has shown that can outperform the expert and the system alone, because high performance degradation happens in the automatic extraction of minutiae compared to the manual extraction done by human experts. This could be even more relevant in palmprints.…”
Section: • Delta D Was Found In All Cases In the Ulnar Area Of The Dimentioning
confidence: 99%
See 2 more Smart Citations
“…(Montesanto et al, 2007) have studied the fingerprint verification based on the fuzzy logic, where they combined the results obtained using three different methods of minutiae extraction: the sequential method, the reactive agent and the neural classification system. (Puertas et al, 2010) studied the performance of a fingerprint recognition technology, in several practical scenarios of interest in forensic casework. First, the differences in performance between manual and automatic minutiae extraction for latent fingerprints were presented.…”
Section: Other Approachesmentioning
confidence: 99%